Preparation of mucoahesive tablets of famotidine by wet granulation method and its in-vitro testing - Zainab Alvi; Hira Sharmeen; Alina Ayub; Attia Shahid; Hafiza Nida Dildar; Mahnoor Imtiaz; Iqra Ejaz (AMMANIF, 2020)
Objective: Famotidine is a histamin H2-receptor antagonist.The aim and objective of the present work is to formulate and evaluate mucoadhesive tablets of famotidine. It is also foused on the selection of mucoadhesive polymer & its activity in various combinations & ratios. The poor bioavialability & shorter half-life suffice the development of controlled release mucoadhesive formulation. Method: Mucoadhesive tablets each containing 20mg of famotidine were prepared by conventional wet granulation method employing as mucoadhesive materials. A batch of 50 tablets was prepared, in each case a blend of 1 gm of famotidine with different polymers addition in different strengths with required 40mg lactose as diluent achieved after titration which were then grannulated along with a solvent blend if water and ethyl alcohol. Results: The flow properties of all five batches were in between fair and passable. Hardness of tablets ranged from 6.9-8.2 kg/cm2 and the percentage friability was between 0.25-0.79 %. The drug content uniformity in the mucoadhesive tablets was 96.49-104.81%. The surface pH study was within the range from 6.7-7.4. From all formulations, over 20% of the famotidine was release within first hour of dissolution study. In the present study the formulation FT04 (tragacanth & HPMC ) has shown cumulative percent drug release of about 80.762% in 12 h. Conclusion: From the results we concluded that formulation containing famotidine with HPMC & tragacanth has given better drug release property than the other four formulations & the wash-off test has shown that this formulation (FT04) has better mucoadhesive property.